Burden of Colovesical Fistula and Changing Treatment Pathways: A Systematic Literature Review. Issue 5 (31st October 2022) - Froiio, Caterina; Bernardi, Daniele; Asti, Emanuele; Bonavina, Giulia; Conti, Andrea; Carmignani, Luca; Bonavina, Luigi
Abstract : Purpose: Colovesical fistula (CVF) is a rare complication of sigmoid diverticulitis causing significant morbidity and quality of life impairment. Aim of this study was to analyze contemporary literature data to appraise the current standard of care and changes of treatment algorithms over time. Materials and Methods: A systematic review of the literature on surgical management of CVF was conducted through PUBMED, EMBASE, and COCHRANE databases, according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement guidelines. Results: Fourteen papers published between 2014 and 2020 and including 1061 patients were analyzed. One-stage colonic resection with primary anastomosis, with or without loop ileostomy, was the most common surgical procedure. A laparoscopic or robotic approach was attempted in 39.5% of patients, and conversion rate to open surgery was 7.8%. Clavien-Dindo grade ≥3 complication rate, 30-day mortality, and recurrence rate were 7.4%, 1.5%, and 0.5%, respectively. Conclusions: Minimally invasive sigmoidectomy with primary anastomosis is safe and should be the first-choice approach for CVF. Bladder repair is not necessary after a negative intraoperative leak test. A standardized perioperative care can improve clinical outcomes and reduce the length of hospital stay and the duration of Foley catheterization.